Non-equilibrium transport in submicron GaAs devices - Tiwari S.C. (My University, 2025)
A heuristic model in which partial local quasi-equilibrium and ballistic transport simultaneously exist is proposed to clarify the meaning of ballistic behaviour. Velocity overshoot in submicron active device lengths is also discussed. Present model accounts fairly well for recent experimental results in which only a fraction of the total number of electrons move ballistically. © 1987 Taylor & Francis Group, LLC.